Ograniczanie barier prawnych i administracyjnych w polityce transgranicznej Unii Europejskiej (Politeja, 2020)
Resolving Legal and Administrative Obstacles in the EU Cross‑border Policy In the face of the crises in the European Union, it has become necessary to review the EU cohesion policy. This new approach can be seen in the recently introduced solutions, which are aimed at the development of cross‑border regions and the elimination of disproportions between them. However, they are not effective enough. Therefore, it is proposed to use further instruments in order to enforce changes in the legal and institutional environment in the regions. This idea is extended in the proposal for a regulation of the European Parliament and of the Council on a mechanism to resolve legal and administrative obstacles in a cross‑border context, which enables a direct application of law of one member state in a cross‑border region of the neighbouring country. The functioning of such mechanism will be a test of the durability of European integration and at the same time will verify if the Polish legal and political system belongs to modern Europe.